Persistently Elevated Soluble Triggering Receptor Expressed on Myeloid Cells 1 and Decreased Monocyte Human Leucocyte Antigen DR Expression Are Associated With Nosocomial Infections in Septic Shock Patients. (24th February 2023) - Venet, Matthieu; Bidar, Frank; Derive, Marc; Delwarde, Benjamin; Monard, Céline; Hengy, Baptiste; Jolly, Lucie; Rimmelé, Thomas; Lukaszewicz, Anne-Claire; Monneret, Guillaume; Venet, Fabienne
Abstract : OBJECTIVES: Sepsis-acquired immunosuppression may play a major role in patients' prognosis through increased risk of secondary infections. Triggering receptor expressed on myeloid cells 1 (TREM-1) is an innate immune receptor involved in cellular activation. Its soluble form (sTREM-1) has been described as a robust marker of mortality in sepsis. The objective of this study was to evaluate its association with the occurrence of nosocomial infections alone or in combination with human leucocyte antigen-DR on monocytes (mHLA-DR). DESIGN: Observational study. SETTING: University Hospital in France. PATIENTS: One hundred sixteen adult septic shock patients as a post hoc study from the IMMUNOSEPSIS cohort (NCT04067674). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Plasma sTREM-1 and monocyte HLA-DR were measured at day 1 or 2 (D1/D2), D3/D4, and D6/D8 after admission. Associations with nosocomial infection were evaluated through multivariable analyses. At D6/D8, both markers were combined, and association with increased risk of nosocomial infection was evaluated in the subgroup of patients with most deregulated markers in a multivariable analysis with death as a competing risk. Significantly decreased mHLA-DR at D6/D8 and increased sTREM-1 concentrations were measured at all time points in nonsurvivors compared with survivors. Decreased mHLA-DR at D6/D8 was significantly associated with increased risk of secondary infections after adjustment for clinical parameters with a subdistribution hazard ratio of 3.61 (95% CI, 1.39–9.34; p = 0.008). At D6/D8, patients with persistently high sTREM-1 and decreased mHLA-DR presented with a significantly increased risk of infection (60%) compared with other patients (15.7%). This association remained significant in the multivariable model (subdistribution hazard ratio [95% CI], 4.65 [1.98–10.9]; p < 0.001). CONCLUSIONS: In addition to its prognostic interest on mortality, sTREM-1, when combined with mHLA-DR, may help to better identify immunosuppressed patients at risk of nosocomial infections.